(untitled) (International Journal of Nursing Education, 2019)
Introduction : Changing technologies & expanding knowledge are increasing the responsibilities of nurses in complex health care environment. Nursing students take maximum responsibility of providing care in the inpatient department of any nursing college across the world in their professional career and express the most vulnerable group to exposure to all types of blood borne pathogens. Methodology: A pre experimental one group pre test post test design was used for the study. The subjects were 5o basic b.sc nursing students selected by non probability conveniences sampling technique. Structured teaching programme (STP) was administered after the assessment of pre test knowledge on universal precaution. Post intervention knowledge was assessed on the 7 day of the administration of STP through the same structured knowledge questionnaire. Result: The study shows that the out of 50 samples most of the students 32(64%) was having average knowledge, 15(30%) of samples were having poor knowledge and 3(6%) of the samples were having good knowledge. Pre test mean score was 19.46 with 3.53 of SD. After administering structured teaching programme 45 (90%) samples were having good knowledge, 5(10%) of the samples were having average knowledge and none of the samples were having poor knowledge. The post test mean score was 28.96 with 2.51 SD with a mean difference of 9.5 as evidence from‘t’ value of 15.57 at 49 df at < 0.05 level of significance. The independent‘t’ test depicts that only gender is associated with the pre test knowledge score, else no demographic variable show any significant association with their knowledge regarding universal precaution. Conclusion: The study concluded that structured teaching programme was effective in increasing the knowledge regarding universal precaution among Basic B.sc Nursing students. Findings of the study focuses that there should be such type of teaching programme for all the health care workers so that they can practise according to the knowledge and prevent the risk from infectious materials.